Biosorption of heavy metals by obligate halophilic fungi. (May 2018) - Bano, Amna; Hussain, Javaid; Akbar, Ali; Mehmood, Khalid; Anwar, Muhammad; Hasni, Muhammad Sharif; Ullah, Sami; Sajid, Sumbal; Ali, Imran
Abstract: The presence of heavy metals in the environment poses a serious threat to human health. Remediation of this problem using microorganisms has been widely researched to find a sustainable solution. Obligate halophilic fungi comprising Aspergillus flavus, Aspergillus gracilis, Aspergillus penicillioides (sp. 1), Aspergillus penicillioides (sp. 2), Aspergillus restrictus and Sterigmatomyces halophilus were used for the biosorption of cadmium, copper, ferrous, manganese, lead and zinc. The metals were supplemented as salts in potato dextrose broth for the growth of obligate halophilic fungi and incubated for 14 days. The supernatant and biomass were obtained by the acid digestion method. The biosorption was screened by atomic absorption spectroscopy. All tested fungi showed moderate to high adsorption of heavy metals, amongst which A. flavus and S. halophilus showed the best average adsorption of all heavy metals studied, with an average of 86 and 83%, respectively. On average, Fe and Zn are best removed from the liquid media of obligate halophilic fungi, with an average of 85 and 84%, respectively. This pioneering study of biosorption by obligate halophilic fungi using inexpensive media in stagnant conditions provides a cost-effective environmental solution for the removal of heavy metals. Highlights: First report of using obligate halophilic fungi for biosorption of heavy metals. Cadmium, copper, ferrous, manganese, lead and zinc were effectively removed from their medium by obligate halophilic fungi. A. flavus and S. halophilus showed best performance for the biosorption of heavy metals. Over all, Fe and Zn were most removed by obligate halophilic fungi. This study provides a cost effective solution of removing heavy metals.